Recommendations to editors to strengthen the peer review process in their scientific journal - Rodríguez-Yunta, Luis; Tejada-Artigas, Carlos-Miguel (Anuario ThinkEPI, 2016)
This article provides an analysis of the critical aspects that editors must consider when managing the peer-review process. While the evaluators assure the quality of a journal, the editor(s) must take steps to improve the process with two main objectives: promoting academic recognition and establishing communication and training tools. In this paper the authors offer concrete recommendations for pursuing these objectives.